SYNTAX, SYNTACTIC STRUCTURES, AND SENTENCE: AN ANALYTICAL STUDY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Syntax, a core component of linguistic theory, examines rules governing sentence structure. Syntactic structures dictate the way words combine to form coherent sentences. This article analyzes key syntactic concepts and sentence structure theory. The paper also explores the evolution of syntax in linguistic history and its implications for language processing.